Comparação entre velocidade crítica e limiar anaeróbio em corrida aquática - da Silva, Leandro Albuquerque (2006)
The comparison between critical velocity and anaerobic threshold has not been investigated in deep water running. Therefore, the aim of this study was to compare these two variables in this activity. Ten subjects of both sexes (23.1 ± 2.2 years, 174.0 ± 10.0 cm, 66.5 ± 18.7 kg) and without previous practice in the activity were submitted to: 1) two to four familiarization sessions; 2) a progressive test, starting with velocity of 0.15 m.s-1 and increments of 0,05 m.s-1 every three minutes; 3) three tests of constant velocities in different days, with velocities ranging from 0.25 to 0.40 m.s-1. The comparison between anaerobic threshold (velocity at 3.5 mM) and critical velocity (identified by three different equations) was performed by analysis of variance and the Bland-Altman method. No significant differences were identified among the variables (p = 0.28), however, the limits of agreement provided by the Bland-Altman plots were very large (between -0.054 e +0.080 m.s-1). These results suggest caution when using the critical velocity to estimate the anaerobic threshold.